A new Epipleoneura Williamson, 1915 (Zygoptera, Coenagrionidae) from northern Brazil and notes on E. venezuelensis Rácenis, 1955 - Pessacq, Pablo; Anjos-Santos, Danielle; Carvalho, Fernando Geraldo; Calvão, Lenize Batista; Mendoza-Penagos, Cristian Camilo; Juen, Leandro (Zootaxa, 2022)
Epipleoneura lencionii sp. nov. is erected based on specimens from Acre State (holotype: 10º7′38.5″S; 67º38′6.7″W, 12.ix.2017, Miguel, T.B. leg). Additional material collected in Minas Gerais was also studied, but subsequently was lost in a fire at the National Museum of Rio de Janeiro. We compared the new species with E. venezuelensis Rácenis, 1955. Epipleoneura lencionii differs from E. venezuelensis by the orientation of the lateral lobes on the male epiproct and by the shape of the posterior lobe of the prothorax of the female. The distribution of the species is analyzed and notes on the reproductive behavior of the genus are provided.